Experimental study on effect of effect time of supercritical CO2 fracturing fluid on mechanical properties of sandstone. (9th November 2021) - Li, Zhihang; Hu, Xiong
Abstract: Supercritical CO2 fracturing is a novel hydro-free fracturing technology, which has the characteristics of minor damage to reservoirs and higher efficiency. During the process of fracturing, the CO2 fracturing fluid will infiltrate into the pore of rock, resulting in the change of rock mechanics properties. The rock samples were drilled from the same layer, then the supercritical CO2 fracturing fluid was used to soak the rock samples to measure the changes of rock mechanical properties under different soaking time. When the pore pressure is 0 MPa, the fracture initiation stress of rock sample is about 40% of its peak strength, and with the increase of pore pressure, the elastic stage decreases and the plastic stage increases, while the pore pressure reaches 31 MPa, the core fracture initiation stress is about 20% of its peak strength. The results show that with the longer CO2 soaking time, the shorter elastic stage with the longer plastic stage and the weaker compressive strength, the smaller elastic modulus, and the higher Poisson's ratio. This indicates that the strength of rock decreases gradually with the increase of injection time in supercritical CO2 fracturing process, which is conducive to the formation of longer fractures.